Analisis Kesesuaian Penggunaan Lahan di Kecamatan IV Jurai Kabupaten Pesisir Selatan terhadap Sistem Informasi Geografis - Limdrawati, Cika; AhyuniAhyuni, Ahyuni (TSAQOFAH, 2026)
IV Jurai Subdistrict in Pesisir Selatan Regency has experienced population growth that has affected regional development and given rise to various spatial planning problems, particularly related to land use change. This study aimed to analyze land use change, assess the conformity of land use with the Regional Spatial Plan (Rencana Tata Ruang Wilayah / RTRW), and identify the spatial distribution of land use changes by village in IV Jurai Subdistrict. The research employed a descriptive quantitative method using on-screen digitization to produce land use maps through overlaying data from 2016 and 2020. Land use change analysis and the assessment of conformity with the RTRW were conducted using the overlay intersect method, including to obtain the geographic locations and areas of land use change across 20 villages in IV Jurai Subdistrict. The findings show that land use in 2016 and 2020 was dominated by forest, settlements, dry fields, rice fields, and coastal sand, with relatively insignificant changes in other categories. The level of conformity between land use and the RTRW reached 74.37%, while 10.83% was categorized as non-conforming, particularly in areas experiencing land conversion. Salido Sari Bulan Village recorded a land use conversion of 32.1 hectares from forest to dry fields, reflecting the dominance of forest areas and the main livelihood of the population as dry-field farmers. These findings emphasize that the dynamics of land use change in IV Jurai Subdistrict need to be taken into account in spatial planning and area management in order to maintain a balance between development needs and environmental sustainability.